Process-based modeling of soil nitrous oxide emissions from United States corn fields under different management and climate scenarios coupled with evaluation using regional estimates - Xia, Yushu; Wander, Michelle M.; Quiring, Steven M.; Yuan, Shanshui; Kwon, Hoyoung (Frontiers in Environmental Science, 2022)
Direct emissions of soil nitrous oxide during a growing season (N2Ogs) can be quantified with process-based models considering interactions between management, climate, and soil moisture when key data are available. We validated soil moisture estimates, a known data gap, before calibration of crop growth and soil organic matter decay coefficients used by an adapted ‘CENTURY/DAYCENT-model’ in the U.S. Corn Belt. There is good agreement between soil moisture estimates and the North American Soil Moisture Dataset during the growing season (R2 = 0.68) but overestimation in winter-spring (R2 = 0.22). Estimated N2O-emissions from corn-based biofuels scenarios considering rotation, fertility, tillage, and weather were verified with corresponding field observations from 55 studies. Both ranked N2Ogs-emissions corn > wheat > soybean. Model underestimation of cover crop emissions was tied to overestimation of pre-season soil moisture and, likely, loss of N2 or leaching. Estimates and observations of N2Ogs-emissions also suggest flux is greater after anhydrous ammonia than urea application and from tilled than non-tilled fields. Only modeled differences were statistically significant. Modeled and observed flux after organic and inorganic fertilizer amendment did not differ due to variability. Regionalized weather scenarios indicate hotspots for N2Ogs loss can occur where crop N uptake is limited during dry years and commonly occur in eastern states in wet seasons. Model-derived N2Ogs-emission factors (EFs) (0.91±0.12%) were not significantly lower than literature (1.07±0.57%) or Tier-1 (1%) values. Modeled results provided valuable spatial insights into N2Ogs-emissions that will be improved by more accurate prediction of non-crop-season soil moisture and fertilizer inputs.